Long‐term presence and habitat use of Cuvier's beaked whale (Ziphius cavirostris) in the Central Tyrrhenian Sea. (27th May 2015) - Arcangeli, Antonella; Campana, Ilaria; Marini, Luca; MacLeod, Colin D.
Abstract: Cuvier's beaked whale ( Ziphius cavirostris, G. Cuvier 1823) is a poorly known species and many international agreements have asked for a better understanding of its biology for conservation purposes. In the present study, systematic cetacean surveys were carried out from ferries along a trans‐regional fixed transect in the Central Tyrrhenian Sea (Civitavecchia, Latium – Golfo Aranci, Sardinia), just outside the southeastern border of the Pelagos Sanctuary. This research provided long‐term, consistent data on Cuvier's beaked whale during two research periods (1990–1992 and 2007–2011). The objective of the research was to compare the presence, distribution and habitat use of Cuvier's beaked whale between the two investigated periods. Summer data (June–September) from the two periods were compared in terms of frequency of sightings, group size and spatial distribution related to the main ecogeographical features. A presence‐absence model (generalized additive modelling) was performed to predict habitat suitability in the two study periods. The results highlight long‐term site fidelity of Cuvier's beaked whale in the Central Tyrrhenian Sea with encounter rates comparable to the ones reported for other key areas. Separate suitability models based on 1990s and 2000s data appeared to work for each individual time period but differences were evident between the two periods, indicating changes in habitat selection over time. Our findings of the study appear to expand the definition of suitable beaked whale habitat and underline how the temporal scale of the analysis can affect the results in habitat studies. Moreover, this research highlights the importance of the Central Tyrrhenian Sea marine region for Cuvier's beaked whale and the ability of continuous monitoring to identify changes in cetacean frequency and distribution, necessary for adaptive conservation management approaches.